2020
DOI: 10.3390/soc10040083
|View full text |Cite
|
Sign up to set email alerts
|

Sense of Place and Belonging in Developing Culturally Appropriate Therapeutic Environments: A Review

Abstract: The connection the Māori, the Indigenous people of Aotearoa-New Zealand, have to the land is threatened by the effects of colonisation, urbanisation and other factors. In particular, many Māori suffer significant health and wellbeing inequalities compared to the non-Māori population. In an effort to reduce such inequalities, there is a growing consciousness of the need to better understand the cultural and place-specific determinants that affect the health and wellbeing of population groups in different enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 46 publications
(50 reference statements)
1
20
0
Order By: Relevance
“…Sustainability 2021, 13, x FOR PEER REVIEW 2 of 23 differ between Māori and non-Māori; the Western approach emphasises personal dysfunction and socio-economic inequalities, while Māori concerns focus on the wider cultural factors affecting the community as a whole [13]. Research indicates that health inequalities can be better understood by focusing on the social and cultural determinants of health and by considering holistic notions of well-being [14][15][16]. This article highlights the need to have a more robust understanding of Mātauranga Māori (Māori knowledge) to better address the social and cultural determinants of health and well-being.…”
Section: Indigenous Knowledgementioning
confidence: 99%
See 2 more Smart Citations
“…Sustainability 2021, 13, x FOR PEER REVIEW 2 of 23 differ between Māori and non-Māori; the Western approach emphasises personal dysfunction and socio-economic inequalities, while Māori concerns focus on the wider cultural factors affecting the community as a whole [13]. Research indicates that health inequalities can be better understood by focusing on the social and cultural determinants of health and by considering holistic notions of well-being [14][15][16]. This article highlights the need to have a more robust understanding of Mātauranga Māori (Māori knowledge) to better address the social and cultural determinants of health and well-being.…”
Section: Indigenous Knowledgementioning
confidence: 99%
“…Some studies explain this connection to land as place attachment, often defined as genus loci, which attaches people to the essence or spirit of a certain place [27]. In the context of Aotearoa-New Zealand, the disconnection from ancestral land or tūrangawaewae (place of belonging, standing and identity) disrupts the way in which Māori connect to place and limits their ability to adapt to the endemic landscape, where they sought protection, guidance, understanding, knowledge, identity, health and well-being, ultimately leading to adverse health and well-being outcomes [15]. This disconnection is explained by some as a result of colonial appropriation, commodification and privatisation of land as well as the forceful expulsion of local populations from their ancestral lands and suppression of alternative forms of production and consumption [28,29].…”
Section: Indigenous Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…An essential aspect of RM and its practices is the locally specific nature of healers and the connection to place, their whenua (landscape), iwi (tribe), hapū (sub-tribe) and whānau (extended family). While many researchers stressed the importance of the concept of place [ 31 , 32 , 33 , 34 , 35 ], few studies mention the importance of self, body, place and landscape [ 36 , 37 , 38 ]. Central to this understanding, three dimensions of Māori knowledge—whakapapa (genealogy) as a way of knowing things, understandings of time, and the importance of the spoken word rather than visual representation—are used to demonstrate how Māori identify themselves, conceptualise the body as an arbiter of interaction with the environment, and create landscape through place naming.…”
Section: Rongoā Māorimentioning
confidence: 99%
“…Our students engaged with internalised critical theory REFLECTING on their buildings (Figure 6). Much of the learning experience was heightened by being physically located in the space, promoting social encounters and active participation of body and senses [42]. Students reported that scale, complexity, aesthetics, and sensory experience deepened the engagement with the physical icon.…”
Section: Discipline Student Commentsmentioning
confidence: 99%